2015
DOI: 10.1186/2197-425x-3-s1-a871
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume as a Marker of Sepsis in Patients Admitted to Intensive Therapy

Abstract: Sanchez-Calzada et al.: Mean platelet volume as a marker of sepsis in patients admitted to intensive therapy. Intensive Care Medicine Experimental 2015 3(Suppl 1):A871.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Several studies have demonstrated the predictive utility of MPV in sepsis 9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] however;, there is little reported bibliography that compares platelet kinetics in critically ill patients with and without sepsis, a critical situation to be demonstrated since several non-infectious diseases can also potentially increase platelet size.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the predictive utility of MPV in sepsis 9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] however;, there is little reported bibliography that compares platelet kinetics in critically ill patients with and without sepsis, a critical situation to be demonstrated since several non-infectious diseases can also potentially increase platelet size.…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez-Calzada et al, en un estudio prospectivo con 202 pacientes, determinaron que el VMP inferior a 7,7 fl es una herramienta útil para descartar etiología infecciosa del síndrome de respuesta inflamatoria sistémica (9). En 2015, Ates et al, realizaron un estudio de casos y controles intentando determinar si el VMP y la razón VMP/contaje plaquetario podían determinar si el síndrome de respuesta inflamatoria sistémica se debía a procesos sépticos, sin éxito ya que los valores de sensibilidad y especificidad tanto del VMP y la razón VMP/contaje plaquetario fueron bajos y sin significancia estadística (10).…”
Section: Vmp Y Sepsisunclassified
“…MPV rising is useful in cardiovascular and cerebrovascular thromboembolic events [15], heart failure [16], infective endocarditis [17], venous thromboembolism [18]. MPV is helpful in sepsis diagnosis [19], course monitoring, and prognosis [11,20].…”
Section: Introductionmentioning
confidence: 99%